Pengaruh Model Pembelajaran Discovery Learning Terhadap Keaktifan Siswa Pada Pembelajaran PAI SMAN 1 Tanjung Mutiara Agam - Cania, Rani; Arsya, Fajriyani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was conducted at SMAN 1 Tanjung Mutiara Agam with the aim of researching because of the lack of courage of students in asking and answering questions from teachers. In addition, when the learning process is taking place, there are still many students who play with their cellphones and do not pay attention to the teacher who is explaining in front, there are health factors that affect student learning activity, and students are also less motivated and less ready to show their seriousness in learning Islamic religious education. This is due to the lack of use of learning models that have not been able to foster enthusiasm and motivation in students in receiving the lessons given, in addition, the source of knowledge in this learning process is still dominated by teachers so that students rarely play an active role. This study aims to determine how much influence the discovery learning model has on the learning activity of class XI F.2 students in Islamic religious education subjects. This study is a quantitative study using the Quasi Experimental Design design. The sample in this study amounted to 33 people with the sampling technique used was purposive sampling. The sample was class XI F.2. Data collection techniques using questionnaires and documentation, while data analysis techniques using the Validity Test formula with the product moment correlation formula, Reliability Test with the Alpha Cronbanch formula, Normality Test Kolmogrov Smirnov statistical test, Homogeneity Test, and continued with Hypothesis Test. From the results of the research and data analysis, the calculation of the t test was obtained 0.0013 <0.005 at a significant level of sig value <0.005 so that the hypothesis stated that there was an influence of the discovery learning model on the learning activity of Islamic religious education students in class XI F.2 SMAN 1 Tanjung Mutiara Agam.